Management of temporomandibular disorders: a rapid review of systematic reviews and guidelines. Issue 9 (September 2022) - Tran, C.; Ghahreman, K.; Huppa, C.; Gallagher, J.E.
Abstract: Temporomandibular disorders (TMD) impact a significant proportion of the population. Given the range of management strategies, contemporary care should be evidence-informed for different TMD types. A knowledge-to-action rapid review of systematic reviews published in the past 5 years and guidelines published in the past 10 years concerning the management of TMD was conducted. The Cochrane, Embase, MEDLINE, PEDro, and PubMed databases were searched. A qualitative data analysis was undertaken, with quality assessment completed using the AMSTAR 2 checklist. In total, 62 systematic reviews and nine guidelines considering a range of treatment modalities were included. In concordance with current guidelines, moderate evidence supports a multi-modal conservative approach towards initial management. Contrary to existing guidelines, occlusal splint therapy is not recommended due to a lack of supporting evidence. The evidence surrounding oral and topical pharmacotherapeutics for chronic TMD is low, whilst the evidence supporting injected pharmacotherapeutics is low to moderate. In concordance with current guidelines, moderate quality evidence supports the use of arthrocentesis or arthroscopy for arthrogenous TMD insufficiently managed by conservative measures, and open joint surgery for severe arthrogenous disease. Based on this, a management pathway showing escalation of treatment from conservative to invasive is proposed.